2021
DOI: 10.1097/mat.0000000000001415
|View full text |Cite
|
Sign up to set email alerts
|

Downsizing of a Pulsatile Total Artificial Heart—The Effect on Hemolysis

Abstract: A downsized version of the ReinHeart total artificial heart (TAH) was developed. Hemocompatibility needs to be revised since the operating point of the downsized TAH has changed to a higher pump frequency to accomplish the same cardiac output. A mock circulation loop was designed, containing a left side for hemocompatibility testing and a right side to mimic realistic work conditions. A protocol for hemolysis testing was established using pooled porcine blood with an operation point of 5 L/min, a mean outlet p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 17 publications
2
11
0
Order By: Relevance
“…This suggests that a small decrease in time-averaged can be achieved by increasing the stroke length and decreasing the heart rate. This points towards the same conclusion drawn by both Syncardia 32 and ReinHeart 55 : an increase in heart rate due to downsizing the pump resulted in higher levels of shear stress and haemolysis. The method of reducing shear stresses observed in this study is at odds with the outcome found for increasing washout rate, suggesting that a trade-off would have to be made between shear stress levels and washout performance.…”
Section: Discussionsupporting
confidence: 76%
“…This suggests that a small decrease in time-averaged can be achieved by increasing the stroke length and decreasing the heart rate. This points towards the same conclusion drawn by both Syncardia 32 and ReinHeart 55 : an increase in heart rate due to downsizing the pump resulted in higher levels of shear stress and haemolysis. The method of reducing shear stresses observed in this study is at odds with the outcome found for increasing washout rate, suggesting that a trade-off would have to be made between shear stress levels and washout performance.…”
Section: Discussionsupporting
confidence: 76%
“…ac.biomed successfully produced the Aachen test rig for pulsatile devices 20,21 demonstrated by reproducible results for the control pump BPX‐80. It achieved a mgNIH value of 5.42 mg/100 L, comparable to previous BPX‐80 hemolysis studies with a range of 2.6–6.6 mg/100 L for porcine 20,21,23–27 and 2.4–7.1 mg/100 L for bovine blood 18 …”
Section: Discussionmentioning
confidence: 99%
“…Pooling blood, although acceptable, is not ideal, because it induces hemolysis, changes erythrocyte resistance against trauma, 19 and limits the study of additional parameters. The Aachen rig was developed to test the pulsatile Reinheart TAH and uses compliance chambers with inflatable silicon bellows to maintain low blood volume 20,21 . The aim herein was to evaluate the in vitro hemolysis of the Realheart® TAH V11C left pump prototype (V11C) with porcine blood in the Aachen rig at one operating point, to enable performance comparison with literature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Upon cessation of bleeding, anticoagulation therapy with a heparin infusion (goal activated partial thromboplastin time of 40 to 60 s) and antiplatelet therapy (aspirin 81 to 324 mg) must be initiated, with eventual bridging to warfarin (target international normalized ratio of 2.5 to 3.0) 11. Postoperative anemia is common in TAH patients and is most commonly due to bleeding and hemolysis caused by mechanical valve sheering 7,10. However, because patients receive TAH support as BTT, transfusion of blood products should be limited to avoid foreign antigen exposure.…”
Section: Syncardia Tah System Implantation and Operationmentioning
confidence: 99%